2003
DOI: 10.1002/ijc.11578
|View full text |Cite
|
Sign up to set email alerts
|

Incidence trends of adult primary intracerebral tumors in four Nordic countries

Abstract: Brain tumors are some of the most lethal adult cancers and there is a concern that the incidence is increasing. It has been suggested that the reported increased incidence can be explained by improvements in diagnostic procedures, although this has not been totally resolved. The aim of our study was to describe the incidence trends of adult primary intracerebral tumors in four Nordic countries during a period with introduction of new diagnostic procedures and increasing prevalence of mobile phone users. Inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
70
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 113 publications
(82 citation statements)
references
References 34 publications
10
70
0
2
Order By: Relevance
“…44,45 In general, CNS tumors were most often noted in women, a finding that has also been reported by other groups. 46,47 The predominance of germ cell and neuroepithelial tissue tumors in men and meningeal tumors in women agrees with results that have been previously reported. 48,49 This gender predominance could be attributed to sex hormones and genetic differences between men and women.…”
Section: -40supporting
confidence: 91%
“…44,45 In general, CNS tumors were most often noted in women, a finding that has also been reported by other groups. 46,47 The predominance of germ cell and neuroepithelial tissue tumors in men and meningeal tumors in women agrees with results that have been previously reported. 48,49 This gender predominance could be attributed to sex hormones and genetic differences between men and women.…”
Section: -40supporting
confidence: 91%
“…The observed number of cases in the study population is approximately the number we expected based on reported incidence in the Nordic countries (24). Blood samples were taken a minimum of 5 years before cancer diagnosis, lessening but not precluding the likelihood that IGF levels were influenced by the tumor.…”
Section: Discussionmentioning
confidence: 78%
“…An association between breast cancer and meningioma has been reported, with an elevated risk of meningioma among women with a previous diagnosis of breast cancer and an elevated risk of breast cancer among women with a previous diagnosis of meningioma (3,4), suggesting common genetic or environmental risk factors. The incidence of glioma is, in contrast, f1.5 times greater in men than women (2,5). The higher incidence in men becomes evident around the age of female menarche, reaching a maximum around the age of menopause and diminishing thereafter (6).…”
Section: Introductionmentioning
confidence: 90%